Letter from Richard Adolf Zsigmondy to Georg Bredig, January 1900 - Zsigmondy, Richard Adolf (1900)
Richard Adolf Zsigmondy (1865-1929), an Austrian colloidal chemist who won the Nobel Prize for Chemistry in 1925, tells Georg Bredig (1868-1944) that he would like to cite his work in an upcoming publication. Zsigmondy additionally compliments Bredig on his work with inorganic ferments.
Keywords: Zsigmondy, Richard; Bredig, Georg, 1868-1944; Colloids; Chemistry, Inorganic; Nobel Prize winners; Zsigmondy, Richard Adolf, 1865-1929